The problems of the research on the professional language of journalists - Vysotskaya, И.В. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
In the context of the problem of interaction between the media and society, the issues of researching the professional language of journalists, in particular, are studying speech and describing the metalanguage of modern Russian journalism, are relevant. The analysis of the author`s own file cabinet and the data of the National Corps of the Russian Language allowed to highlight the actual processes in the sociolect of journalists: activation of new foreign language borrowings (kontent, n’yusmejker) and changes in the semantic structure of words borrowed earlier (speaker, expert). Some cases of semantic aberration of the actual Russian words are noted. These phenomena demonstrate the ways of replenishing the professional language both due to external borrowing, and due to the internal resources of the national language (polysemy), as well as the possibility of the subsequent exit of professionalism beyond the scope of sociolect. The author’s own experience is presented in lexicographic description of the metalanguage of the modern Russian journalist on the basis of spoken speech research of the editors of Russian media